Screendance Narratives from around the Mediterranean Sea - Mikou, Ariadne (The International Journal of Screendance, 2020)
The European Mediterranean appears to be an active key player for the production and circulation of screendance. Focusing this research on the pre-pandemic state of screendance in Italy, France, Greece and Spain and employing a methodology of one-to-one interviews, this text examines the art policies that have been in place for potentially supporting the production of screendance, the ways that spectatorship and social engagement kept on growing and the predictions for the yet-to-come evolution of the form in a context disassociated from, yet applicable to the on-going pandemic. Although screendance is understood differently among the interviewees – curators of major festivals such as DAN. CIN. LAB., Festival International De Vidéo Danse De Bourgogne, COORPI/La Danza in 1 minuto, Cinematica Festival, Stories We Dance International Videodance Contest, Choreoscope - The International Dance Film Festival of Barcelona and the formerly known Athens Video Dance Project – International Dance Film Festival – the aim of this research is to create knowledge regarding the heterogeneous landscape of screendance in the European Mediterranean as well as a broader understanding of the shifting Mediterranean culture.